Quantum oscillations in coupled orbits networks of (BEDT-TTF) salts with tris(oxalato)metallate anions - Laukhin, Vladimir N.; Audouard, Alain; Fortin, Jean-Yves; Vignolles, David; Prokhorova, Tatyana G.; Yagubskii, Eduard B.; Canadell, Enric (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Band structure calculations relevant to bis-ethylenedithio-tetrathiafulvalene-based charge transfer salts containing tris(oxalato)metallate anions, with generic formula (BEDT-TTF)4A[M(C2O4)3]·Solv, where A is a mo-novalent anion, M is a trivalent cation and Solv is a solvent, suggest that their Fermi surface is liable to achieve networks of compensated orbits coupled by magnetic breakdown. Even though this picture accounts for quantum oscillations spectra of a number of these compounds, puzzling results can be noticed in several cases, pointing to the possibility of Fermi surface reconstruction at low temperature.